PREVALENCE OF INTESTINAL HELMINTHIC INFECTIONS AND ASSOCIATED RISK FACTORS - Sah, R B; Paudel, I S; Baral, R; Poudel, P; Jha, N; Pokharel, P K (Indian Journal of Community Health, 2013)
Background: Parasitic infection is still a serious public health problem in the world, especially in developing countries, and represents a major cause of morbidity and mortality in childhood and among high-risk groups in most parts of the world. Objectives: To measure the prevalence of intestinal helminthic infections and to identify risk factors associated with helminthic infection among the school children of Itahari Municipality. Materials and Methods: The cross sectional study was conducted in Grade VI, VII and VIII in schools of Itahari Municipality. Stratified random sampling method was applied to choose the schools and the study subjects. Semi-structured questionnaire was administered to the study subjects and microscopic examination of stool was done.The Chi-square test was used to measure the association of risk factors and intestinal helminthic infections. Results: Overall intestinal helminthic infection was found to be 13 percent. Taenia species was found high (6.5%) in comparison to other worms i.e. Hookworm (3%), Ascaris lumbricoides (2%) and Trichuris trichiura (1.5%). The use of soap and water after defecation showed lower prevalence of helminthic infections (8%) than only uses water (34.2%). The helminthic infection was also seen lower who wear sandal (2%) than who do not wear sandal (23.8%). Conclusions: The result of this study indicated that intestinal helminthic infections among school going children is a common health problem and was seen more who do not use soap to wash hand, do not wear sandal and having unhygienic skin, nail and clothes.